GE_GERICHTE C/19931/2011 vom 11. Juli 2012 - GE Cour de justice (2012)
; CAS CLAIR ; SUCCESSION | Examen de l'existence d'un cas clair dans cadre d'une procédure successorale. | CPC.86. CPC.257. CC.604. CC.634. CC.2.2. CC.602.1. CC.560. CC.608. CC.617